Penggunaan Frasa Verbal dalam Teks Berita Detik.com Terbitan September 2025 - Maulani Apriliani; Muhammad Anis Rofiq; Fellice Ariqah Marsa; Aisyah Nur Faizah; Endah Sawitri; Asep Purwo Yudi Utomo; Tutik Wijayanti; Chaerunnissa Chaerunnissa (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2026)
This study aims to identify, analyze, and describe in depth the types of coordinating verbal phrases (FV) and subordinating verbal phrases (FV) contained in Detik.com news texts published in September 2025. Based on the fundamental role of language as a means of communication and social interaction (syntax), the object of research is focused on FV as a grammatical unit that has a verb core and functions as a predicate. This study uses a qualitative descriptive method with a syntactic theoretical approach. Data collection was carried out through the technique of listening and taking notes on Detik.com news texts, while data analysis was applied using the distribution method, where the determining tool comes from the linguistic elements themselves. The results of the study showed the discovery of a total of 13 verbal phrases divided into 3 coordinating FVs and 10 subordinating FVs (including the patterns Adv + V, V + Adv, V + Adj, and V + N). In detail, 3 coordinating FVs, 3 FVSs with Adv + V pattern, 2 FVSs with V + Adv pattern, 2 FVSs with V + Adj pattern, and 3 FVSs with V + N pattern were found. This finding emphasizes the importance of understanding phrase structure in maintaining clarity of meaning. This research is expected to improve readers' literacy understanding and serve as a scientific reference for similar linguistic studies.